Major achievements of the United Nations. - United Nations. Department of Public Information ([1998].)
The United Nations was established in the aftermath of a devastating war to help stabilize international relations and give peace a more secure foundation.
Amid the threat of nuclear war and seemingly endless regional conflicts,peace-keeping has become an overriding concern of the United Nations. In the process,the activities of blue-helmeted peace-keepers have emerged as the most visible role associated with the world organization.
The United Nations,however,is much more than a piece-keeper and forum for conflict resolution. Often without attracting attention,the United Nations and its family of agencies are engaged in a vast array of work that touches every aspect of people's lives around the world.
Child survival and development -- Environmental protection -- Human rights -- Health and medical research -- Alleviation of poverty and economic development -- Agricultural development and fisheries -- Education -- Family planning -- Emergency and disaster relie -- Air and sea travel -- Peaceful uses of atomic energy -- Labour and worker's rights -- The list goes on -- Here in brief, is sampling of what the United Nations organizations have accomplished since 1945 when the world organization was founded.
Typescript.
Also available at http://www.un.org/Overview/achieve.html
Last updated September 1996.
Keywords: United Nations -- Awards; Nobel Prizes -- History